A sadly troubled history : the meanings of suicide in the modern age - Weaver, John C. (McGill-Queen's/Associated Medical Services studies in the history of medicine, health, and society ;, 2009)
More people die by suicide each year than by homicide, wars, and terrorist attacks combined. Witnesses and survivors are left perplexed and troubled. Doctors, clinical psychologists, and social workers try to deal with it through their professional routines; sociologists and psychiatrists attempt to provide theoretical explanations of it.